(untitled) (Historia, 2021)
The struggle to liberate the continent of Africa from colonialism was a profound and all-time consuming one for Africans during the second half of the twentieth century and as such, this history needs to be documented accurately in whatever form for the benefit of posterity. Amaral Cabral opined that the people’s struggle for national liberation and independence from imperialist rule constituted one of the essential characteristics of contemporary history.